(Im)mobility, digital technologies and transnational spaces of belonging: an ethnographic study of Somali migrants in Cape Town - Brudvig, Ingrid (Social Anthropology, 2019)
This study draws on ethnographic research with Somali migrants in Cape Town to explore the intersection of (im)mobility, physical and virtual space and new configurations of belonging in a digital world. It investigates the gendered politics and ethics of being and belonging in a world of mobility and migration where digital technologies have become significant to social organisation and sociality, both within and across borders. The dissertation presented probes the reasons why policies and technologies that were expected to create more fluid movement and more open societies have been met with the hardening of national borders, and a parallel rise in global trends towards anti-immigration, control of identities and fear of difference, which have manifested in South African society. This dissertation concludes that a combination of legal frameworks related to migrants and refugees, public infrastructures and cultural factors exert a strong influence on Somali migrants’ access to rights in South Africa, identity and social reproduction, and transnational belonging. Social exclusion may be a catalyst for Somali migrants’ transnational engagements in which digital technologies are a significant driver of heightened group consciousness and belonging. In many ways, the rise of online social networks and information capital have taken off among Somali migrants because of their tremendous social organising power in the absence of formal institutions, limited political and social belonging in host countries, and in the context of vastly integrated transnational diaspora networks which sustain economic and social lives. As such, Somali migrants live at the margins of (im)mobility – in-between physical and virtual spaces – leading to the navigation of “frontier-ness”, challenging taken-for-granted identities. While most studies about mobility and migration focus on citizenship and belonging from a legalistic or deterministic standpoint – solidifying prescribed notions of “Somaliness” or other factors of identity affiliated with nationhood or citizenship – there is a need to dig deeper to understanding what it means to navigate and, indeed perform, belonging via gendered technologies of mobility. Participation in social life through online networks and in transnational spaces often challenges common assumptions that identity is necessarily linked to particular places. However, this research simultaneously demonstrates the ways in which nations and borders continue to be emphasised in a world of flows. Contrary to popular assumptions that the internet is transnational, borderless and disassociated with place, this research argues that nation-places – enacted through hubs and nodes – continue to be salient. In this context, it is important to understand how digital technologies intersect with identity, culture and socialnorms offline and online among diverse communities to support new configurations of agency and empowerment in an increasingly digital world. In this light, this dissertation looks at how digital technologies, such as the internet, emerge as a force of mobility, situated in contrast to stark forces of immobility which seek to limit the movement of people. Not only does the internet close distance between geographies, it also closes distances in access to information and networks of support, such as financial assistance, social capital and caregiving. Experiences of mobility (offline and online) have been both empowering and liberating. However, mobility is also circumscribed and limited by new forms of social control and manipulation at all levels of society. Despite the profoundly transnational and borderless context of the internet, “traditional” cultural frameworks and identities, such as nationality and gender, continue to be salient markers of online identity, just as they are offline. This study argues that digital technologies are culturally constituted frontier spaces characterised by various layers of (im)mobility through which belonging is navigated and performed.